(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In modern science fiction literature, the global epidemic motif has evolved from simple descriptions of the fight against viruses to complex narrative structures, where the pandemic serves as a tool for exploring a wide range of social and philosophical problems. Based on the achievements of modern science, the authors create multilevel texts that explore not only the biological, but also the social aspects of global epidemics. The article analyzes the works of such authors as Mira Grant, Peter Watts, Margaret Atwood, Emily St. John Mandel, Colson Whitehead and Stephen King, in which the pandemic becomes a catalyst for social change, ethical dilemmas and philosophical reflections on the nature of man and society. The variety of approaches to portraying the pandemic in modern fiction demonstrates a deep understanding of the possible consequences of a global catastrophe for humanity.